2004
DOI: 10.1111/j.1527-3458.2004.tb00021.x
|View full text |Cite
|
Sign up to set email alerts
|

E‐SAR‐94010 (LipoEsar®): A Pleiotropic Lipoprotein Compound with Powerful Anti‐atheromatous and Lipid Lowering Effects

Abstract: E-SAR-94010 (LipoEsar) is a natural product extracted from the marine species S. pilchardus, by means of non-denaturing biotechnological procedures. The main chemical ingredient of LipoEsar is a lipoprotein (60-80%) whose micelle structure probably mimics that of physiological lipoproteins involved in lipid metabolism. In preclinical studies LipoEsar has shown to be effective in (a) reducing blood cholesterol (Cho), triglyceride (TG), uric acid (UA), and glucose (Glu) levels, as well as liver alanine aminotran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…In a group of patients with dementia with associated hyperlipidemia whose treatment was supplemented with LipoEsar, we observed an effect similar to that seen in hyperlipidemic patients [16,17,20,22] (Table 2). dyslipidemia (419 patients with 750 mg/day LipoEsar for three months) [19] and healthy volunteers (500 mg/day LipoEsar for two weeks) [13]. In healthy subjects supplemented with LipoEsar, we observed an increase in lymphocyte subset markers CD3, CD4, CD25, CD26, CD28, and CD56, and a reduction in CD8 and HLA-DR antigen expression.…”
Section: Atheroma Plaque Basalmentioning
confidence: 76%
See 3 more Smart Citations
“…In a group of patients with dementia with associated hyperlipidemia whose treatment was supplemented with LipoEsar, we observed an effect similar to that seen in hyperlipidemic patients [16,17,20,22] (Table 2). dyslipidemia (419 patients with 750 mg/day LipoEsar for three months) [19] and healthy volunteers (500 mg/day LipoEsar for two weeks) [13]. In healthy subjects supplemented with LipoEsar, we observed an increase in lymphocyte subset markers CD3, CD4, CD25, CD26, CD28, and CD56, and a reduction in CD8 and HLA-DR antigen expression.…”
Section: Atheroma Plaque Basalmentioning
confidence: 76%
“…The therapeutic response to LipoEsar in chronic hyperlipidemic patients is apolipoprotein E (APOE) genotype-dependent. The best responders are those patients with APOE-3/3 > APOE-3/4 > APOE-4/4 [13,17,[19][20][21]. LipoEsar is highly effective as a co-adjuvant of statin therapy in hyperlipidemic patients, enabling a reduction in statin dose, and avoiding the deleterious effects produced by statin treatment.…”
Section: Study Characteristics Results-conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, we have demonstrated that APOE and CYP variants (2D6, 2C9, 2C19, 3A4/5) influence basal CHO levels and the therapeutic response of AD patients to hypolipemic compounds [ 10 , 14 , 17 ]. In a larger study with 1345 hypercholesterolemic AD patients (CHO > 220 mg/dL), we investigated the pharmacogenetics of cholesterol response to Atorvastatin (10–20 mg/day) plus SardiLipin (E-SAR-94010; LipoEsar ® ; Ebiotec, Bergondo, Spain) (500 mg/day), a nutraceutical compound of the ProteoLipin/LipoFishin family [ 57 ], with lipid-lowering effects and anti-atherosclerotic and neuroprotective properties (Patent ID: P9602566) [ 10 , 36 , 58 ]. In the whole sample, the response rate (RR) was 78.96% responders (CHO < baseline levels) and 21.04% non-responders (CHO ≥ baseline levels) after one month of treatment ( Figure 4 ).…”
Section: Pharmacogenetics Of Hypercholesterolemia In Alzheimer’s Dmentioning
confidence: 99%